2020
DOI: 10.3390/cells9091937
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana cbp80, c2h2, and flk Knockout Mutants Accumulate Increased Amounts of Circular RNAs

Abstract: Circular RNAs (circRNAs) are the products of the non-canonical splicing of pre-mRNAs. In contrast to humans and animals, our knowledge of the biogenesis and function of circRNAs in plants is very scarce. To identify proteins involved in plant circRNA generation, we characterized the transcriptomes of 18 Arabidopsis thaliana knockout mutants for genes related to splicing. The vast majority (>90%) of circRNAs were formed in more than one variant; only a small fraction of circRNAs was mutant-specific. Five tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, we compared the sources used by other plant circRNA databases and we chose those that met our criteria. In total, we utilized third-party data from eight studies (100 SRA files) and two datasets (110 SRA files) from our previous studies ( 11 , 12 ). All analyzed datasets are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we compared the sources used by other plant circRNA databases and we chose those that met our criteria. In total, we utilized third-party data from eight studies (100 SRA files) and two datasets (110 SRA files) from our previous studies ( 11 , 12 ). All analyzed datasets are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In plants, the biogenesis of circRNAs has not been thoroughly investigated ( Figure 3 ). In Arabidopsis , the accumulation of circRNAs is significantly increased in the splicing-related mutants cbp80 , c2h2 , and flk ( Philips et al., 2020b ), suggesting that the biogenesis of plant circRNAs is also affected by splicing factors ( Figure 3 A).
Figure 3 Proposed model of circRNA biogenesis in plants.
…”
Section: Biogenesis Of Circrnas In Plantsmentioning
confidence: 99%
“…Splicing factor proline/glutaminerich and non-POU domain-containing octamer-binding protein mediated the Alu-independent circRNA production (64). Capbinding protein 80, C2HC zinc fingers superfamily protein, and flowering locus kh domain were related to the processes of splicing and the proper order of the exons, which expression levels were negative with the circRNA production (14). Serine and Arginine Rich Splicing Factor 10 (SRSF10) promoted circ-ATXN1 production by binding to the 5′-end and 3′-end of its pre-mRNA (95).…”
Section: Possible Biogenesis Mechanism Of Host Circrnasmentioning
confidence: 99%
“…However, increasing evidence showed that various circRNAs commonly existed in natural organisms with conservative sequences among different species. Until now, the identification of circRNAs and their possible roles have been explored in more than 20 species, including Archaea (8), plants (11,13,14), viruses (15)(16)(17)(18)(19), insects (20,21), and mammals (12,22,23). A small subset of circRNAs with different activities was confirmed to play vital roles in regulating individual growth and development, environmental stress, innate immunity, and disease occurrence (13,(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%